Synthesis, crystal structure and theoretical studies of aryltellurenyl tetramethylthiourea(tmtu) iodine complexes: Ph-Te(tmtu)I (1) and beta-naphtyl-Te(tmtu)I (2) - Lang, E. S.; Ledesma, G. N.; Abram, U.; Vega-Teijido, M.; Caracelli, I.; Zukerman-Schpector, J. (Oldenbourg Verlag, 2006)
(1) C11H17IN2STe, Mr = 463.83, P2(1)/n, a 7.6582(8), b = 13.8008(9), c = 15.026(3) angstrom, beta = 96.233(12)degrees, Z = 4, R-1 = 0.0318. (2) C15H19IN2STe, Mr = 513.88, P2(1)/n, a = 8.434(5), b = 11.697(5), c = 18.472(5) angstrom, beta = 98.556(5)degrees, Z = 4, R-1 = 0.0236. The synthesis of the aryltellurenyl N,N',-tetramethylthiourea (tmtu) iodide has been performed by ligand exchange with potassium iodide and the corresponding aryltellurenyl(tmtu) bromide. In both structures the tellurium atom is primarily three-coordinated, being bonded to a carbon atom of the organic ring and, in directions nearly perpendicular to the Te-C bond, to one tmtu sulfur atom and one iodine. In addition there are Te...secondary bonds, joining the molecules in centrosymmetric dimers, which in turn are joined through C-H...1 and C-H... S interactions, in (1) and (2), respectively.
Keywords: tellurium(II); tetramethylthiourea; supramolecular; X-ray diffraction; single crystal structure analysis